APPLICATION OF WORD ANIMATION MEDIA IN IMPROVING READING ABILITY IN ELEMENTARY SCHOOL STUDENTS: Penerapan Media Animasi Kata Dalam Meningkatkan Kemampuan Membaca Pada Siswa Sekolah Dasar - Akhmad Bayu Adi Priyanto; Akhtim Wahyuni (Journal for Technology and Science, 2024)
This research aims to find out the application of word animation media on reading ability in elementary school students. This research is a research literature study with a qualitative descriptive approach. In this study the type of research used is the study of literature. Data collection techniques by collecting data from some literature related to the influence of word animation media on students' reading ability in elementary school. The data analysis that researchers use is observation. Based on the results of the discussion shows that the planning carried out by elementary schools in implementing animation media education is by designing the mission vision of the school based on animation media. Because this vision and mission is used as a plan of an activity in the future for the realization of the realization of an education in the future